Maternal depressive symptomatology in México: National prevalence, care, and population risk profiles. - Filipa de Castro; Jean Marie Place; Aremis Villalobos; Betania Allen-Leigh (Instituto Nacional de Salud Pública, 2015)
Objective. This study estimates the prevalence of depressive symptomatology (DS) in women with children younger than five years of age, examines detection and care rates and probabilities of developing DS based on specific risk profiles. Materials and methods. The sample consists of 7 187 women with children younger than five drawn from the Ensanut 2012. Results. DS prevalence is 19.91%, which means at least 4.6 million children live with mothers who experience depressive symptoms indicative of moderate to severe depression. Rates of detection (17.06%) and care (15.19%) for depression are low. DS is associated with violence (OR=2.34; IC95% 1.06-5.15), having ≥4 children, having a female baby, older age of the last child, low birth weight, food insecurity, and sexual debut menor que 15 years old (p menor que 0.01). Accumulated probability of DS, taking into consideration all risk factors measured, is 69.76%. It could be reduced to 13.21% through prevention efforts focused on eliminating violence, food insecurity, bias against having a female baby, and low birth weight. Conclusions. DS is a compelling public health problem in Mexico associated with a well-defined set of risk factors that warrant attention and timely detection at various levels of care.